2012
DOI: 10.1007/s11356-012-1218-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polychlorinated naphthalenes in stack gas emissions from waste incinerators

Abstract: Nine typical waste incinerating plants were investigated for polychlorinated naphthalene (PCN) contents in their stack gas. The incinerators investigated include those used to incinerate municipal solid, aviation, medical, and hazardous wastes including those encountered in cement kilns. PCNs were qualified and quantified by isotope dilution high resolution gas chromatography-high resolution mass spectrometry techniques. An unexpectedly high concentration of PCNs (13,000 ngNm −3 ) was found in the stack gas em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…It has been speculated that the unintentional formation and emission of PCNs from industrial activities will become much more important than previously because the manufacture and use of PCNs and PCBs as industrial chemicals has ceased in many countries (Hogarh et al, 2012). PCN emissions have been investigated from a number of industrial thermal processes, including waste incineration (Takasuga et al, 2004;Noma et al, 2006;Sakai et al, 2006;Hu et al, 2012), iron and steel production (Liu et al, 2012a,b), nonferrous smelting processes (Sinkkonen et al, 2004;Nie et al, 2011;Nie et al, 2012a,b), coking industries , and cement production . Comparing PCN emissions from industrial thermal processes could provide data that are useful for understanding environmental PCN burdens and the risks associated with exposure to PCNs around industrial plants.…”
Section: Concentrations and Teqs Of Pcn Emissions From Different Indumentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that the unintentional formation and emission of PCNs from industrial activities will become much more important than previously because the manufacture and use of PCNs and PCBs as industrial chemicals has ceased in many countries (Hogarh et al, 2012). PCN emissions have been investigated from a number of industrial thermal processes, including waste incineration (Takasuga et al, 2004;Noma et al, 2006;Sakai et al, 2006;Hu et al, 2012), iron and steel production (Liu et al, 2012a,b), nonferrous smelting processes (Sinkkonen et al, 2004;Nie et al, 2011;Nie et al, 2012a,b), coking industries , and cement production . Comparing PCN emissions from industrial thermal processes could provide data that are useful for understanding environmental PCN burdens and the risks associated with exposure to PCNs around industrial plants.…”
Section: Concentrations and Teqs Of Pcn Emissions From Different Indumentioning
confidence: 99%
“…Although many case studies of PCN emissions from industrial processes have been performed (Ba et al, 2010;Liu et al, 2010Liu et al, , 2011Nie et al, 2011;Hu et al, 2012;Liu et al, 2012c, Liu et al, 2012d, a comprehensive summary of PCN emission factors from industrial thermal sources has not been produced. We have summarized the PCN emission factors and annual emissions from fourteen industrial thermal processes (metallurgical processes, combustion processes, and mineral product production) in Table 2.…”
Section: Pcn Emission Factors and Emission Estimatesmentioning
confidence: 99%
“…In addition to municipal solid waste incinerators (MSWIs) (Abad et al, 1999;Jansson et al, 2008;Hu et al, 2013), various metallurgical industries, particularly SeCu, are becoming increasingly important sources of PCNs (Ba et al, 2010;Nie et al, 2011;Liu et al, 2012a,b). Liu et al (2014) summarized PCN emission factors and annual emissions for 14 industrial thermal processes, and suggested that SeCu potentially contributes a large proportion of PCN emissions in China, having comparable emission factors to those found for MSWIs.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent organic pollutants (POPs), such as polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), and polychlorinated naphthalenes (PCNs), can be formed unintentionally during industrial thermal processes, including waste incineration Hu et al, 2013b), iron ore sintering (Grochowalski et al, 2007;Liu et al, 2012a), and secondary non-ferrous metal smelting (Weber et al, 2008;Ba et al, 2009). Once emitted from a plant where industrial thermal processes are performed, these unintentionally produced POPs (UPPOPs) could potentially have great impacts on the ambient environment and human health because of their high toxicities, persistence, and abilities to bioaccumulate.…”
Section: Introductionmentioning
confidence: 99%